Metodologia de ensaios dielétricos para sistemas de isolação sólido-líquido aplicados a transformadores de potência - Bueno, Daniela Maia (2021)
This master thesis presents contributions to the field of dielectric tests for solidliquid insulation systems applied to power transformers. It is intended that this methodology serves as a reference guide to obtain experimental results. In this context, it is necessary to design and build the structure necessary to carry out the tests in two configurations, consisting of electrode arrays that present geometries that seek to replicate real conditions of the transformer. In order to validate such configurations, computational simulations based on finite element analysis are performed. Due to the need to ensure a reliable statistical characterization of the test, a methodology for defining the minimum number of samples to be used in dielectric breakdown tests is also proposed. In addition, the procedures for sample preparation of paper and insulating oil are presented, as well as the application of withstand voltage of standardized lightning impulse and alternating voltage at commercial power frequency. The assembly of the test configurations is carried out and a pre-test procedure is proposed. Finally, the Weibull distribution is described with the purpose of analyzing the breakdown voltage data obtained in the dielectric tests. From the proposed methodology, it becomes possible, in the future, to carry out dielectric tests and the definition of design curves, as well as the safety margins for the dielectric design using different solid and liquid insulating materials, in addition to providing results and conclusions that enable the design and manufacture of power transformers.